Kinerja optimal bank syariah melalui implementasi manajemen strategi yang berkelanjutan - Azzam, Muhammad (Maliki Interdisciplinary Journal, 2025)
The importance of implementing sustainable strategic management in achieving optimal performance of Islamic banks, which must balance financial achievement with social responsibility. Islamic banks do not only operate to achieve profitability, but also play a role in supporting economic development and social welfare. Strategic management involves the process of planning, organizing, implementing, and controlling bank resources effectively to achieve long-term goals. Research shows that Islamic banks that are able to adopt innovative, adaptive strategies and adhere to Islamic principles are more likely to achieve optimal performance. In addition, effective risk management and innovation in products and services also play an important role in increasing the competitiveness and sustainability of Islamic bank operations amidst increasingly fierce competition.